Optical coherence tomography and autofluorescence findings in chronic phototoxic maculopathy secondary to snow-reflected solar radiation - Shukla, Dhananjay (Indian journal of ophthalmology, 2015)
A professional mountain trekker presented with gradual, moderate visual decline in one eye. The subnormal vision could not be explained by the examination of anterior and posterior segment of either eye, which was unremarkable. Optical coherence tomography and autofluorescence imaging revealed subtle defects in the outer retina, which correlated with the extent of visual disturbance. A novel presentation of retinal phototoxicity due to indirect solar radiation reflected from snow in inadequately protected eyes of a chronically exposed subject is reported.